Dendrophysiological plant strategies of Poincianella pyramidalis (Tul.) L.P. Queiroz after wood herbivory in semiarid region of Paraíba - Brazil - Santana, Otacilio Antunes; Encinas, Jose Imana (Acta Scientiarum. Biological Sciences, 2016)
The increase in Equus africanus asinus Linnaeus population in semiarid areas of Northeast Brazil had significant impacts on wild and rural areas. The objective of this work was to analyze the herbivory of E. africanus asinus on Poincianella pyramidalis (Tul). L.P. Queiroz and determine the dendrophysiological strategies P. pyramidalis used during and after damage caused by E. africanus asinus. The selected areas have significant populations of P. pyramidalis with amplified importance value higher than 50%. Two areas were established: one control and another experimental, with presence of E. africanus asinus. The study was carried out from 2001 to 2015. The evaluated variables of P. pyramidalis were: sap flow, basic density, diameter, volume, biomass and leaf area index. The increase of abandoned E. africanus asinus in semiarid areas resulted in impact and responses from P. pyramidalis. This plant species compensates for biomass losses and physiological activities reduction with two strategies: i) increase in the belowground biomass stock, and ii) increase in sap flow in undisturbed branches.